Efficacy and safety of acupuncture for the treatment of insomnia in breast cancer patients: A systematic review and meta-analysis - Yupeng Weng; Xuanrong Ren; Zheyan Zu; Lu Xiao; Min Chen (Elsevier, 2024)
Background: Breast cancer-related insomnia is one of the most common symptoms in patients with breast cancer, and acupuncture has been increasingly used in the treatment. However, there has been no meta-analysis that specifically explores the efficacy and safety of acupuncture in treating insomnia related to breast cancer. Objective: The aim of this review was to systematically analyze the existing literature through a meta-analysis to evaluate the effectiveness and safety of acupuncture for breast cancer-related insomnia. Methods: Six medical databases were comprehensively searched for previous randomized controlled trials (RCTs) up to April 2024. The Pittsburgh Sleep Quality Index (PSQI) score was the primary outcome. The secondary outcomes include the Insomnia Severity Index (ISI), Sleep Onset Latency (SOL), Wake After Sleep Onset (WASO), Total Sleep Time (TST), and Sleep Efficiency (SE), and the later four outcomes were measured by Actiwatch and sleep diary, respectively. Results: A total of seven articles with 434 participants were included. The meta-analysis revealed that acupuncture produced a significant improvement in the total PSQI score (MD 95 %CI = -2.16[-2.88, − 1.45], P < 0.001), but had no statistical significance on ISI scores compared with controls (MD 95 %CI = -1.53[-3.97, 0.91], P = 0.22). From the Actiwatch, there was no substantial disparity observed in the enhancement of Sleep Onset Latency (SOL) (MD 95 %CI = -6.40[-13.19, 0.39], P = 0.06), Wake After Sleep Onset (WASO) (MD 95 %CI = -1.45[-7.09, 4.20], P = 0.62), or Total Sleep Time (TST) (MD 95 %CI = 3.54 [-4.71, 11.79], P = 0.40) between the experimental group and the control group. However, a significant distinction was observed in Sleep Efficiency (SE) improvement (MD 95 %CI = 2.43 [0.14, 4.72], P = 0.04). From the sleep diary, there was a significant difference in the amelioration of SOL (MD 95 %CI = -9.15[-16.48, − 1.81], P = 0.01), TST (MD 95 %CI = 29.92 [16.74, 43.10], P < 0.001), and SE (MD 95 %CI = 4.57 [1.92, 7.23], P = 0.0007) between the experimental group and the control group. However, no significant divergence was observed in the improvement of WASO (MD 95 %CI = 4.53[-4.81, 13.87], P = 0.34). All reported acupuncture-related adverse events were mild in severity. Conclusions: Acupuncture can partially alleviate insomnia symptoms in breast cancer patients. Moreover, acupuncture is safe and may serve as a dependable alternative therapy in clinical settings. Owing to the limited number of studies included, potential biases of heterogeneous interventions, and methodological weaknesses of long-term follow-up, more high-quality RCTs with large sample sizes should be conducted to evaluate acupuncture treatment.